Tinjauan Kriminologis terhadap Tindak Pidana Korupsi Bantuan Cadangan Beras Pemerintah (Studi Putusan No. 26/Pid.Sus-TPK/2024/PN Amb) - Kristian Adi Nurpranata; Rehnalemken Ginting (Lembaga Pengembangan Kinerja Dosen, 2025)
Judicial sentencing through court judgments often does not align with the ideal objectives of sentencing itself, especially in cases involving corruption crimes. Judgment Number 26/Pid.Sus-TPK/2024/Pn Amb serves as an example of the disparity between the prosecutor's sentence recommendation and the final verdict delivered by the judge. In this case, the prosecutor demanded a seven-year prison sentence, while the judge sentenced the defendant to only two years and six months, with the mitigating consideration that the defendant did not personally benefit from the state's financial loss. Therefore, the writer conducts an analytical review of this judgment through a criminological perspective and judicial reasoning. The analysis of Judgment Number 26/Pid.Sus-TPK/2024/Pn Amb is intended to assess how well the judgment fulfills the ideal function of law.